GIS Integration into Geography Curriculum in Türkiye: A Case Study Evaluation - Dündar, Erkan; Kaya, Niyazi (Acta Paedagogica Vilnensia, 2023)
The integration of technology into education is a complex process with many dimensions, and there are many steps that need to be taken for this integration to be successful. One of the most important of these is the integration of information and communication technologies into the curriculum. The aim of this study is to shed light on the updates that can be made in the curriculum by examining the geography curriculum implemented in Türkiye and last revised in 2018 in terms of GIS integration, which is the first technology that comes to mind when the words geography and technology come side by side, and to present the steps of creating a GIS application for this learning outcome by restructuring a learning outcome within the scope of a case study. In the light of the findings obtained in this study, which was designed with the case study method, one of the qualitative research designs, it was concluded that GIS is included in only a few chapters in the geography curriculum, and there is only one learning outcome for which the use of GIS technology is recommended. According to this result, the restructured version of the learning outcome 10.4.1, which is the only learning outcome that is foreseen to be given GIS support in the geography curriculum, according to the understanding of learning with technology and a sample GIS application, is presented.
Keywords: GIS; Geography education; technology integration; technology; curriculum